Land governance re-arrangements: The one-country one-system (OCOS) versus one-country two-system (OCTS) approach - Cheonjae Lee; Walter Timo de Vries; Uchendu Eugene Chigbu (Administrative Sciences, 2019)
This paper evaluates how land governance is re-arranged in a state re-structuring process. We compare the cases of the (re-)unification of China with Hong Kong with that of West and East Germany. The division and (re-)unification of these states mark different land governance re-arrangements. The China-Hong Kong (re-)unification relied on a one-country two-system (OCTS) approach, while inWest and East Germany, (re-)unification resulted in the creation of a one-country one-system (OCOS). Our key interest is to identify similarities and differences in both cases and the implications of the differences. To support the analysis, we view land governance and (re-)unification from theoretical to practical lenses-structuration theory and the government tools-based approach. This supports the construction of a conceptual and analytical framework, with which we conduct an in-depth exploration to evaluate land governance re-arrangements. We find that the conceptual and analytical framework proves effective for countries, with entirely different land governance regimes, to decide whether to merge or adapt. We do not conclude which approaches for (re-)unification are appropriate to land governance re-arrangements since all countries have different historical contexts and institutional arrangements. Instead, we recommend that governments consider adaptive land governance in signification structures and focus on hierarchical enforcement in legitimation structures. While multi-level land governance in the domination structure phase is strongly required, issue-and-project-based land governance has a pivotal role in providing cross-boundary infrastructures. Nevertheless, further empirical analysis is recommended to verify how and where the re-arrangement processes are initiated and structured.
Keywords: 350; land governance; (re-)unification; transformation; structuration theory; tools of government